APPLICATION OF BIM TECHNOLOGIES IN BUILDING OPERATING ORGANIZATIONS - Zafar Matniyazov; Bakhrom Tulaganov; Zarifjon Adilov; Rustamkhon Khadjaev; Samidullo Elmurodov (Scholar Express Journal, 2024)
This article is dedicated to the application of Building Information Modeling (BIM) technologies in organizations operating buildings. It discusses the use of the Asset Information Model (AIM) for effective data management during the building's operational phase. The advantages of applying BIM are outlined, including enhanced communication, efficient data exchange, minimization of data loss, and improved building maintenance. Special attention is given to creating a Common Data Environment (CDE) and establishing standards for data exchange and management. The paper also discusses processes related to data security, building maintenance, and resource optimization. The use of BIM contributes to improved operational efficiency, reduced costs, and enhanced building resilience throughout their lifecycle.
Keywords: building operation, AIM, data management, data exchange, building lifecycle, maintenance, security, resilience, information space.